Small business management - Pickle, Hal B. (John Wiley and Sons, 1990)
This book is divided into six sections: Entrepreneurship, Small Business Ownership, and Franchising; Establishing the Firm; Managing the Small Business; Management Information and Merchandise Control; Marketing the Product or Service; and The Government and Small Business.